2018
DOI: 10.1007/s00421-018-4007-8
|View full text |Cite
|
Sign up to set email alerts
|

The interactions of physical activity, exercise and genetics and their associations with bone mineral density: implications for injury risk in elite athletes

Abstract: Low bone mineral density (BMD) is established as a primary predictor of osteoporotic risk and can also have substantial implications for athlete health and injury risk in the elite sporting environment. BMD is a highly multi-factorial phenotype influenced by diet, hormonal characteristics and physical activity. The interrelationships between such factors, and a strong genetic component, suggested to be around 50–85% at various anatomical sites, determine skeletal health throughout life. Genome-wide association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 155 publications
0
35
0
2
Order By: Relevance
“…Again, this may be attributable to the decline in bone mineral density starting as early as age 25 years in both men and women. 3 Many respondents commonly recommended scooters for patients who are obese, and obesity was identified as a common characteristic among injured patients. Obese individuals might be injured more commonly because they are more likely to have scooters recommended.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, this may be attributable to the decline in bone mineral density starting as early as age 25 years in both men and women. 3 Many respondents commonly recommended scooters for patients who are obese, and obesity was identified as a common characteristic among injured patients. Obese individuals might be injured more commonly because they are more likely to have scooters recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, although respondents indicated that a patient's lifestyle (sedentary vs active) does not influence their likelihood of recommending scooters, sedentary lifestyle was a more commonly reported characteristic among injured patients. Physical activity improves bone mineral density, 3 a From w 2 goodness-of-fit test, with null hypothesis expecting equal distribution of observations among answer choices, excluding "Other" and/or "Unsure." b Expressed as mean + SD.…”
Section: Discussionmentioning
confidence: 99%
“…Результатом этого исследования стал вывод о том, что ЧСС является фактором риска смерти независимо от физической подготовленности и других потенциальных факторов риска. Высокий уровень физической подготовленности служит сильным предиктором долголетия [12], что обусловлено также положительным влиянием на минеральную плотность кости [14].…”
Section: физическая активность и частота сердечных сокращенийunclassified
“…Other human studies have detected QTL associated with physical traits related to exercise abilities, including maximal oxygen consumption (VO 2max ) (Williams et al 2017), bone density (Herbert et al 2019), and more (Lin et al 2017). The list of possible biological traits affiliated with exercise and their associated QTL is extensive (Sarzynski et al 2016;Lightfoot et al 2018).…”
Section: Introductionmentioning
confidence: 99%